2013
DOI: 10.3791/4401
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Building Nucleic Acid Structures with 3DNA

Abstract: The 3DNA software package is a popular and versatile bioinformatics tool with capabilities to analyze, construct, and visualize three-dimensional nucleic acid structures. This article presents detailed protocols for a subset of new and popular features available in 3DNA, applicable to both individual structures and ensembles of related structures. Protocol 1 lists the set of instructions needed to download and install the software. This is followed, in Protocol 2, by the analysis of a nucleic acid structure, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 35 publications
1
65
0
Order By: Relevance
“…The 80-nucleotide (nt) A-form RNA duplex and 48-nt B-form DNA helix are generated using the latest version (version 2.1) of the program X3DNA. 73 Other RNA structures, such as the 76-nt yeast tRNA Phe (PDB ID: 1TRA 74 ), 58-nt fragment of rRNA and rRNA-protein complex (PDB ID: 1HC8 75 ), and 72-nt Adenine riboswitch (A-riboswitch; PDB ID: 1Y26 76 ), are generated from the Protein Data Bank coordinate files. 77 For the 5BSL3.2:3X complex in the HCV genomic RNA, cell-based viral replication assays 6870 have suggested that the kissing complex is formed between 5BSL3.2 and the SL2 hairpin loop in the 3′X.…”
Section: The Pctbi Modelmentioning
confidence: 99%
“…The 80-nucleotide (nt) A-form RNA duplex and 48-nt B-form DNA helix are generated using the latest version (version 2.1) of the program X3DNA. 73 Other RNA structures, such as the 76-nt yeast tRNA Phe (PDB ID: 1TRA 74 ), 58-nt fragment of rRNA and rRNA-protein complex (PDB ID: 1HC8 75 ), and 72-nt Adenine riboswitch (A-riboswitch; PDB ID: 1Y26 76 ), are generated from the Protein Data Bank coordinate files. 77 For the 5BSL3.2:3X complex in the HCV genomic RNA, cell-based viral replication assays 6870 have suggested that the kissing complex is formed between 5BSL3.2 and the SL2 hairpin loop in the 3′X.…”
Section: The Pctbi Modelmentioning
confidence: 99%
“…We take advantage of a new feature in the 3DNA suite of programs that allows a user to look at multiple structures from a common perspective. 32 The software aligns the individual DNA pathways in the multi-model NMR structure files on a common reference frame. Here we position the G·C base pair at the centers of the three natural operators on the corresponding base pair in the O 1 -containing crystal structure and the highly kinked CG base-pair step at the centers of the symmetric operator models on the corresponding base pair in the O sym crystal complex (PDB entry 1efa 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…We take advantage of another new feature of 3DNA that facilitates the analysis of ensembles of related structures in collecting the components of the local helical axes. 32 The twisting of DNA is based on a discrete ribbon constructed from the origins and reference frames of successive base pairs. 35 In contrast to the twist angle included in the six rigid-body parameters specifying the relative spatial arrangements of successive base pairs, 36 the twist reported here, the so-called twist of supercoiling, can be combined with the writhing number of a closed structure to obtain the correct linking number.…”
Section: Methodsmentioning
confidence: 99%
“…S6B,C). As chemical shifts and NOE patterns were not significantly affected upon magnesium addition, the same dihedral and distances restraints were used to generate a model of Five stems were defined using the 3DNA software (Colasanti et al 2013). Helical axes for the five stems were generated using MOLMOL software and are indicated in pink (Koradi et al 1996).…”
Section: Effect Of Magnesium On Hpi Structurementioning
confidence: 99%
“…Quality factors (Q) and root-mean-square deviations (RMSD) between input and calculated RDCs were calculated with the PALES software for the 10 final converged structures before and after refinement with the opls force field (Table 1; Zweckstetter and Bax 2000). Structures were visualized and analyzed with MOLMOL, Pymol and 3DNA software packages (Koradi et al 1996;Delano 2005;Colasanti et al 2013). …”
Section: Structure Calculationsmentioning
confidence: 99%